Information security applications : 15th International Workshop, WISA 2014, Jeju Island, Korea, August 25-27, 2014 : revised selected papers /: 15th International Workshop, WISA 2014, Jeju Island, Korea, August 25-27, 2014 : revised selected papers. ([2015]) - Unknown
No abstract available